Analisis Kesalahan Penulisan pada Undangan Pernikahan berdasarkan Ejaan yang Disempurnakan (EYD) dan Kamus Besar Bahasa Indonesia (KBBI) - Mattoliang, Ridwan Andi; Ahmad; Rostina (Faculty of Tarbiyah and Teacher Training, 2024)
This study aims to analyze writing errors in wedding invitations based on the rules of the Enhanced Spelling System (EYD) and the Great Dictionary of the Indonesian Language (KBBI). Wedding invitations are an important form of written communication in social life, so errors in writing can disrupt meaning, aesthetics, and the credibility of the event organizers. This research employs a descriptive qualitative analysis method by identifying and classifying various types of writing errors found in wedding invitations circulating in society. The study examines spelling mistakes, word choice, and punctuation errors that do not conform to the EYD and KBBI guidelines. The results indicate that common errors include discrepancies in spelling, incorrect word usage, and improper punctuation placement. These findings are expected to contribute to raising public awareness about the importance of using language in accordance with correct linguistic rules, particularly in writing wedding invitations.